Low-intensity vibrations accelerate proliferation and alter macrophage phenotype in vitro. Issue 5 (21st March 2016) - Pongkitwitoon, Suphannee; Weinheimer-Haus, Eileen M.; Koh, Timothy J.; Judex, Stefan
Abstract: Macrophages are essential for the efficient healing of various tissues. Although many biochemical signaling pathways have been well characterized in macrophages, their sensitivity to mechanical signals is largely unexplored. Here, we applied low-intensity vibrations (LIV) to macrophages to determine whether macrophages could directly transduce LIV signals into changes in the expression of genes and proteins involved in tissue repair. Two different LIV signal frequencies (30 Hz or 100 Hz) were combined with two acceleration magnitudes (0.15 g or 1 g ) to generate four distinct LIV signals that were applied to cultured murine macrophages. All four LIV signals significantly increased macrophage number after 3 days of stimulation with the combination of the smallest acceleration and the highest frequency (0.15 g at 100 Hz) generating the largest response. Compared to non-LIV controls, gene expression of the pro-healing growth factors VEGF and TGF-β increased with all four LIV signals (Day 1). LIV also decreased protein levels of the pro-inflammatory cytokines IL-6, IFN-γ, and TNF-α (Days 1 and 3). These data demonstrate the sensitivity of macrophages to high-frequency oscillations applied at low intensities and may suggest that the benefit of LIV for tissue repair may be based on reducing inflammation and promoting a pro-healing macrophage phenotype.